Photoluminescence of Single GaN/InGaN Nanorod Light Emitting Diode Fabricated on a Wafer Scale - Chan, C; Zhuang, Y; Reid, B; Jia, W; Holmes, M; Alexander-Webber, J; Nakazawa, S; Shields, P; Allsopp, D; Taylor, R (2013)
Nanorod arrays were fabricated on a blue InGaN/GaN single quantum well (QW) LED wafer using nanoimprint lithography. A regular hexagonal lattice of nanorods was made at a pitch of 2 μm producing single quantum disks in the nanorods with diameter of ̃400 nm. Time integrated micro-photoluminescence was performed to investigate the emission properties of top down processed single nanorods at 4.2 K. Microphotoluminescence maps were made to study the spatial isolation of the photoluminescence emission, showing a good contrast ratio between nanorods. Excitation power dependent studies show screening of the quantum confined Stark effect for both the unprocessed wafer and the single nanorod. At low excitation powers, localised states appearing as sharp peaks in the photoluminescence spectrum were visible with a density of approximately four peaks per nanorod. © 2013 The Japan Society of Applied Physics.